9z-z=-1+4z-3-4

Simple and best practice solution for 9z-z=-1+4z-3-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9z-z=-1+4z-3-4 equation:


Simplifying
9z + -1z = -1 + 4z + -3 + -4

Combine like terms: 9z + -1z = 8z
8z = -1 + 4z + -3 + -4

Reorder the terms:
8z = -1 + -3 + -4 + 4z

Combine like terms: -1 + -3 = -4
8z = -4 + -4 + 4z

Combine like terms: -4 + -4 = -8
8z = -8 + 4z

Solving
8z = -8 + 4z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-4z' to each side of the equation.
8z + -4z = -8 + 4z + -4z

Combine like terms: 8z + -4z = 4z
4z = -8 + 4z + -4z

Combine like terms: 4z + -4z = 0
4z = -8 + 0
4z = -8

Divide each side by '4'.
z = -2

Simplifying
z = -2

See similar equations:

| 5XZ=30 | | 5f/5=35/5 | | 2x-4=87-11x | | 7y=-7*7-35 | | 3b^2-b-14=0 | | 20x+10=60 | | 2x+3.4=2x+3.4 | | 3(2x-4)-4x=16 | | 2(0)+(y)-6(0)=30 | | -2x+7=12x-6 | | -11+x=7x+5 | | 0=a^2+14a+36 | | 2y^2+7=5 | | 3=3x-6x^2 | | 17-(4-6z)+4=21 | | 2x^2+10-6=0 | | 3a=15+3 | | x/136=1.5 | | 7x-15=36 | | (2k+1)=5 | | r+n=12.5 | | 3n^2-4=26 | | (5t^2-t+2)+(-4t^2+3t+7)= | | 14b+63= | | 9y^2-8+4y^2+9= | | 151=X-13 | | 6x-5=8x+9 | | 2x+3x+1+2=26 | | (x-2)/x=0.88 | | m^2+6m-31=0 | | 2x=8-5 | | 3/X-(1/2x)=1/4 |

Equations solver categories